Applications of systems dynamic principles to technique and strength training - Schöllhorn, W. I. (Acta Academiae Olympiquae estoniae, 2000)
Highly skilled levels in sports are often associated with an enormous amount of coordinative and strength training. Large numbers of repetitions are often considered a necessity to achieve mastery, and frequentlythese repetitions are related to the same movement. Based on the philosophy of linear causality it is assumed that an athletes` movement will improve towards championship by copying the "ideal" movements as often as possible. Therefore, general "soll-values" (to be achieved) are derived from "ideal" movements, typically defined by means of world class athletes. However, a change in the understanding of causality and problems with the generality of this approach in most recent research lead to rethink the traditional training philosophy. At first glance the concept of ideal movements seems quite plausible. Investigating ideal movements in more detail, two main problems emerge. First, it seems difficult to coincide the philosophy of generality with recent investigations where the individuality of every persons` movement could be shown quantitatively. The second problem is related to the stability of movements and its relationship to an ideal movement. When repeated movements are investigated in more detail and compared with each other, it can be stated that the movements always show fluctuations and it seems almost impossible to produce the same movement twice ([3-5]. This leads to problems with the idea of an ideal movement and to the general question. When the next movement is different from the last anyway, what can be the ideal movement? Suggestions for the solutions of these problems can be derived from the systems dynamic approach. A brief introduction into systems dynamic approach and possible practical consequences to technical and strength training in sport will be discussed subsequently. Source: Acta Academiae Olympiquae estoniae (2000) 8, 67-85.